CYBER THREAT TERRAIN- A RISK MITIGATION STRATEGY (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
In the present scenario, the proliferation of cyber threats poses a significant impact on theorganizations as well as on the individuals. To protect the individuals and organizations fromthe cyber crimes the cyber security has came into existence. This paper explores a concept ofcyber threat terrain, and proposes risk mitigation strategies.